Galectin-3 controls the response of microglial cells to limit cuprizone-induced demyelination - Hoyos, Hernán Carlos (2014)
Galectin-3 (Gal-3) is a β-galactoside-binding lectin that plays an important role in inflammatory and neurodegenerative diseases. Cuprizone (CPZ)-induced demyelination is characterized by the loss of mature oligodendrocytes (OLG) by apoptosis, myelin sheath degeneration and recruitment of microglia and astrocytes to the lesioned area. We compared CPZ-induced demyelination of 8-week-old Lgals3(-/-) vs WT mice. Lgals3(-/-) mice displayed a similar susceptibility to CPZ-induced demyelination up to the fifth week, as evaluated by MBP immunostaining and electronic microscopy. However, OLG progenitors (OPC) generated in CPZ-treated Lgals3(-/-) mice showed diminished arborization, suggesting decreased ability of these cells to differentiate. Surprisingly, while WT mice experienced spontaneous remyelination in the fifth week of CPZ treatment-even though the CPZ diet was maintained up to sixth week-Lgals3(-/-) mice lacked this capacity and suffered continuous demyelination up to the sixth week, accompanied by pronounced astroglial activation. Moreover, after 2weeks of CPZ treatment, WT and Lgals3(-/-) mice showed lower innate anxiety as compared with respective naive mice, but only CPZ-treated Lgals3(-/-) mice showed decreased locomotor activity and exhibited spatial working memory impairment. Expression of Gal-3 increased during CPZ-induced demyelination in microglia but not in astrocytes. While CPZ-treated WT mice displayed heightened microglial activation associated with ED1 expression and pronounced upregulation of the phagocytic receptor TREM-2b, this effect was not observed in CPZ-treated Lgals3(-/-) mice which, in spite of showing an increased number of microglia, these cells evidenced caspase-3 activation. Our results indicate that Gal-3 is expressed in microglial cells to modulate their phenotype, facilitating the onset of remyelination and OLG differentiation.